An overview of the opus of architect Đorđe Đorđević (1921-1940) - Gačić Ivanov, Jelena (Arhitektura i urbanizam, 2024)
In the historiography of modern Serbian architecture, the work of architect Đorđe Đorđević is characterized by evident marginalization. Although he was a public and private architect who collaborated with eminent civil engineers and bourgeois clients, biographical data and a chronology of his activites have not been consistently established. Many of his works were excluded during fragmentary reviews, due to the proxy signing of projects by civil engineers Lazar Kostić and Miloš Antić, in whose technical bureau he worked in the middle of the 1930s. Also, the circumstances that prolonged the recognition of architect Đorđević are his exclusion from professional associations and professional publishing activites; only one recorded exhibition activity and the devastation of his personal legacy during the Allied bombing of Belgrade in 1944. After a short time in the Ministry of Construction, his professional path was marked by private practice, which began with the establishment of a technical bureau with Aleksandar Kapović. From 1929, he operated as an independent certified architect, implementing capital public and residential buildings, one of which was located in Niš. He demonstrated a keen mastery of various stylistic tendencies, but quantitatively he designed a large number of objects in the style of academism. By consulting the Technical Directorate in the Historical Archive of Belgrade and the Ministry of Construction in the Archive of Yugoslavia, as well as other important primary and secondary sources, a systematic overview of Đorđević’s opus was established.